Endoluminal reconstruction of the canine common biliary duct - Zografakis, John G; Jones, Brian T; Ravichardran, Pars; Evancho-Chapman, M.Michelle; Schmidt, Steven P; Arends, Dane; Funk, Karla M; Gingras, Peter (Current surgery, 2003)
Extrahepatic biliary duct injuries such as transections, stenoses, and biliary leaks are well-known complications of upper abdominal surgeries. The popularization of laparoscopic cholecystectomies in the early 1990’s resulted in an increase in the numbers of these reported injuries. The surgical repair of these injuries may be challenging. In this feasibility study, we were presented with the opportunity to evaluate a novel polytetrafluoroethylene (PTFE) covered stent graft that could be useful in common bile duct reconstructions. The long-term goal of this research is to offer the surgeon a new technique for reconstructing the biliary duct or repairing biliary strictures. Seven dogs were originally enrolled in the study. After general endotracheal anesthesia and open cholecystectomy, the common bile duct was identified in each dog. A guide wire was then passed through the neck of the cystic duct, anterograde into the common bile duct, through the Ampulla of Vater and into the duodenum. A stent graft delivery system was placed over the wire, and the covered stent graft was deployed within the lumen of the common bile duct. Study outcomes included graft patency and assessment of the bio-incorporation of the graft and the effectiveness of the graft to drain the biliary system as determined by liver enzyme tests. Three implants were harvested at 1 month, and 2 grafts were harvested each at 3 months and 6 months postoperatively. All of the stent grafts were patent. Liver enzyme tests revealed that all dogs had increased serum levels of alkaline phosphatase, alanine aminotransferase (ALT) serum glutamate pyruvate transaminase (SGPT) and aspartate aminotransferase (AST) serum glutamic oxaloacetic transaminase (SGOT). Four dogs had increased total bilirubin. These increases were all measured in the immediate postoperative period. Peak levels for each measure were reached between 4 and 10 days and then gradually trended toward baselines by 1 month postoperatively. We did not observe meaningful changes in serum albumin or total protein. One dog suffered a tear in the common bile duct due to balloon overinflation. This tear was suture repaired when the graft was implanted. However, bile leakage was found when the graft was harvested at 1 month postoperatively. There appeared to be minimal bio-incorporation of the stent-grafts into the biliary duct wall, and there was no pronounced inflammatory response found in the duct wall or surrounding tissues. We are encouraged by these early results. Additional studies are planned to evaluate a self-expanding PTFE covered stent graft and a percutaneous delivery system.